2016
DOI: 10.1002/mnfr.201600014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced M2 macrophage polarization in high n‐3 polyunsaturated fatty acid transgenic mice fed a high‐fat diet

Abstract: Our results indicate that n-3 PUFAs play a crucial role in macrophage polarization and chemotaxis, and thus regulate the development of HFD-induced tissue inflammation and metabolic derangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
0
25
1
Order By: Relevance
“…A high‐fat diet (HFD) promotes progenitor proliferation and adipogenesis in adipose tissue in rodents prior to a significant increase of body weight . Our results showed that the relative percentage of M1 macrophages in WT‐SVF was about 12% of total SVF compared with a previous study in which nearly 40% was observed when WT mice had a significant body weight gain relative to Fat‐1 mice in an HFD‐induced obesity model . Without HFD challenge, no body weight difference between WT and Fat‐1 mice at the age of 9 to 12 weeks was observed in this study, thus indicating that the mice used for WAP identification were not yet in an obese state; most likely, their adipose tissue was prone to hyperplasia after HFD feeding.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…A high‐fat diet (HFD) promotes progenitor proliferation and adipogenesis in adipose tissue in rodents prior to a significant increase of body weight . Our results showed that the relative percentage of M1 macrophages in WT‐SVF was about 12% of total SVF compared with a previous study in which nearly 40% was observed when WT mice had a significant body weight gain relative to Fat‐1 mice in an HFD‐induced obesity model . Without HFD challenge, no body weight difference between WT and Fat‐1 mice at the age of 9 to 12 weeks was observed in this study, thus indicating that the mice used for WAP identification were not yet in an obese state; most likely, their adipose tissue was prone to hyperplasia after HFD feeding.…”
Section: Discussioncontrasting
confidence: 44%
“…Moreover, previous studies have reported potential adverse effects of inhibiting adipogenesis on metabolism . However, this is not the case for the effects of omega‐3 PUFA . Herein, omega‐3 PUFA reduced the WAP resident population rather than completely abolished WAP numbers and their differentiation to white adipocytes.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…There are limited data on the relationship between oxylipins and various cell polarization and/or adaptation states. Recently, it was shown that various ω-3/ω-6 PUFA diets are able to change the polarization of macrophages [7,8]. There is also evidence that ω-6and ω-3-derived oxylipins are able to modulate the inflammatory phenotype of immune cells, especially macrophages [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Saturated fatty acids are commonly proinflammatory, whereas unsaturated fatty acids are weakly proinflammatory or neutral, and v-3 polyunsaturated fatty acids (PUFAs), such as a-linolenic acid (ALA), eicosapentaenoic acid, and docosahexaenoic acid are anti-inflammatory (5,6). Several anti-inflammatory effects of v-3 PUFAs have been characterized in terms of macrophage function (7)(8)(9), although the underlying mechanisms remain poorly understood.…”
mentioning
confidence: 99%